The Detectives Who Kill: Black Female Detectives in the Works of Oyinkan Braithwaite and Nnedi Okorafor. - Chow-Quesada, Emily (Clues: A Journal of Detection (McFarland & Company))
Works by Oyinkan Braithwaite and Nnedi Okorafor demonstrate the lethal duality of their Black detectives who are also killers. This duality sets the detectives apart, allowing them to pursue justice and defend the rights of others. The analysis shows how African crime fiction by Black female writers in the twenty-first century intertwines gender and sociopolitical discourses.